Pengaruh Fasilitas Belajar Dan Motivasi Belajar Terhadap Prokrastinasi Akademik dan Hasil Belajar Ekonomi Siswa - Puja Stevani; Marwan Marwan (Universitas Negeri Padang, 2021)
This study aims to analyze : 1) The impact of learning facilities on the learning motivationto the student Senior High School Number 1 Batusangkar, 2) The leverage of learning facilities and learing motivation on the academic procrastination to the student Senior High Scholl Number 1 Batusangkar, 3) The effectlearning facilities,learing motivation and academic procrastination on the learning outcome to the student Senior High School Number 1 Batusangkar.the type of research is associative descriptive research. The sampling technique used is proportional random sampling, with 60 samples. The result show that (1) Learning facilities has a positive and significant effect on learing motivation, (2) Learning facilities has a negative and significant effect on academic procrastination, (3) Learning motivation has a negative and significant effect on academic procrastination, (4) Learning facilities has a significant effect on learing outcome, (5) Learningmotivation has a significant effect on learing outcome, (6) Academic procrastinationhas a significant effect on learing outcome, (7) Learning facilities, learing motivation and academic procrastination has a significant effect on learing outcome.Keywords: learning facilities, motivation to learn, academic procrastination